2018
DOI: 10.1093/eurheartj/ehy013
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin clot properties independently predict adverse clinical outcome following acute coronary syndrome: a PLATO substudy

Abstract: AimsTo determine whether fibrin clot properties are associated with clinical outcomes following acute coronary syndrome (ACS).Methods and resultsPlasma samples were collected at hospital discharge from 4354 ACS patients randomized to clopidogrel or ticagrelor in the PLATelet inhibition and patient Outcomes (PLATO) trial. A validated turbidimetric assay was employed to study plasma clot lysis time and maximum turbidity (a measure of clot density). One-year rates of cardiovascular (CV) death, spontaneous myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 40 publications
5
125
1
3
Order By: Relevance
“…Fibrin clot properƟes are clinically-relevant (reviewed in 44,[60][61][62][63][64][65] Examples: inflammatory bowel disease, anƟphospholipid syndrome, rheumatoid arthriƟs, chronic obstrucƟve pulmonary disease Clots with densely-packed fibers, increased sƟffness, and resistance to fibrinolysis are found in cardiovascular and other diseases.…”
mentioning
confidence: 99%
“…Fibrin clot properƟes are clinically-relevant (reviewed in 44,[60][61][62][63][64][65] Examples: inflammatory bowel disease, anƟphospholipid syndrome, rheumatoid arthriƟs, chronic obstrucƟve pulmonary disease Clots with densely-packed fibers, increased sƟffness, and resistance to fibrinolysis are found in cardiovascular and other diseases.…”
mentioning
confidence: 99%
“…Unlike the enhanced platelet reactivity in these patients which reduced from admission to discharge, presumably reflecting the onset of effect of antiplatelet therapy, fibrinolysis in ACS patients appears unaffected by DAPT [15,16]. Our group has previously investigated the effects of P2Y 12 inhibitors on endogenous fibrinolysis and shown that these agents appear to have minimal impact on fibrinolysis [18].…”
Section: Pharmacological Modulation Of Endogenous Fibrinolysismentioning
confidence: 99%
“…In the last 2 years, two large prospective studies have confirmed that impaired fibrinolysis in patients with ACS is a novel independent marker of increased cardiovascular risk [15,16]. In a sub-study of > 4000 patients in the PLATO trial, assessment of fibrin clot lysis using a validated turbidimetric assay revealed that impaired fibrin clot lysis was an independent predictor of adverse outcome in ACS [15]. After adjusting for established cardiovascular risk factors, each 50% increase in lysis time was associated with cardiovascular death/spontaneous MI [Hazard ratio [HR] 1.17, 95% confidence interval (CI) 1.05-1.31; p < 0.01] and cardiovascular death alone [HR 1.36, 95% CI 1.17-1.59; p < 0.001].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This has been addressed in the PLATO substudy 'Fibrin clot properties independently predict adverse clinical outcome following acute coronary syndrome' by Robert F. Storey and colleagues from the University of Sheffield in the UK in 4354 patients. 15 After adjusting for cardiovascular risk factors, each 50% increase in lysis time was associated with cardiovascular death or myocardial infarction, with hazard ratios of 1.17 and 1.36, respectively. Similarly, each 50% increase in maximum turbidity was associated with a 1.24-fold increased risk of cardiovascular death.…”
mentioning
confidence: 97%